Nightwork : a novel [compact disc, unabridged] - Roberts, Nora (Macmillan Audio, 2022)
Harry Booth started stealing at nine to keep a roof over his ailing mother's head. When his mother finally succumbed to cancer, he left Chicago, but kept up his nightwork. He cannot afford to attract attention or get attached. Still, he can't help letting his guard down when he meets Miranda Emerson. But the powerful bond between them cannot last, because not all thieves follow Harry's code of honor. After Harry takes a lucrative job commissioned by Carter LaPorte, LaPorte sees a tool he can use, and decides he wants to own Harry. The man is a predator, and when he strongarms Harry into robbing a Baltimore museum, Harry abandons Miranda cruelly, with no explanation, and disappears. But no matter what name he uses or where he goes, LaPorte casts a shadow over Harry's life. To truly free himself, he must face down his enemy once and for all. Only then can he hope to possess something more valuable than anything he has ever stolen.